2000
DOI: 10.1128/jvi.74.1.228-236.2000
|View full text |Cite
|
Sign up to set email alerts
|

Integrins α2β1 and α4β1 Can Mediate SA11 Rotavirus Attachment and Entry into Cells

Abstract: Most mammalian rotaviruses contain tripeptide amino acid sequences in outer capsid proteins VP4 and VP7 which have been shown to act as ligands for integrins ␣2␤1 and ␣4␤1. Peptides containing these sequences and monoclonal antibodies directed to these integrins block rotavirus infection of cells. Here we report that SA11 rotavirus binding to and infection of K562 cells expressing ␣2␤1 or ␣4␤1 integrins via transfection is increased over virus binding to and infection of cells transfected with ␣3 integrin or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
170
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 67 publications
5
170
0
4
Order By: Relevance
“…To this end, we showed that 8-aa RGD peptides (namely pRGD-Hu, pRGD-Bo, and pRGD-Eq derived from human, bovine, or equine lactadherin, respectively) are endowed with a slight antiviral efficacy. Published studies provide evidence that rotavirus infectivity is not inhibited by RGD peptide, and function-blocking antibodies to RGD-binding integrins do not inhibit rotavirus infection (20,23,53). No evidence for Wa binding to integrins via RGD is available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we showed that 8-aa RGD peptides (namely pRGD-Hu, pRGD-Bo, and pRGD-Eq derived from human, bovine, or equine lactadherin, respectively) are endowed with a slight antiviral efficacy. Published studies provide evidence that rotavirus infectivity is not inhibited by RGD peptide, and function-blocking antibodies to RGD-binding integrins do not inhibit rotavirus infection (20,23,53). No evidence for Wa binding to integrins via RGD is available.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DGE-containing peptides, such as Asp-Gly-Glu-Ala (DGEA), specifically inhibit rotavirus-cell binding and infection mediated by ␣2␤1 (9,20,21,25). Binding by infectious monkey (SA11 and RRV) and human (Wa) rotaviruses to recombinant ␣2␤1 expressed on K562 cells was specifically inhibited by DG-containing peptides and a function-blocking antibody to the ␣2I domain (9,21,23). Therefore, the interaction of rotavirus with ␣2␤1 integrin can be considered a target for the development of antiviral agents aimed at preventing or reducing rotavirus infection.…”
mentioning
confidence: 99%
“…Infection by the majority of rotaviruses is independent of terminal SA, but it might involve subterminal SA (14,22). SA11 binding to ␣2␤1 expressed on K562 cells as a result of transfection specifically resulted in increased infectivity, which was inhibited by cellular treatment with an anti-␣2 MAb (23). Cellular receptors for viruses bind virus via virusspecific proteins, and this binding leads to productive cellular infection.…”
mentioning
confidence: 99%
“…Integrins ␣2␤1, ␣X␤2, and ␣4␤1 were implicated in group A rotavirus cell attachment and entry (11,23), and ␣V␤3 was proposed to mediate rotavirus cell entry (20). Integrin usage by rotaviruses was discovered when VP5* was shown to contain the type I collagen-derived, ␣2␤1 ligand sequence DGE at amino acids 308 to 310, and the fibrinogen-derived ␣X␤2 integrin ligand sequence GPR was identified in VP7 at amino acids 253 to 255 (11).…”
mentioning
confidence: 99%
“…Binding of RV in a mixture of nonsialylated glycolipids from bovine brain and mouse intestine was demonstrated suggesting thatattachment and penetration of the virus dependupon different cellular components, and that the former takes place in two stages, dependent and independent of sialylated compounds at cell surface (Willoughby et al, 1990;Srnka et al, 1992;Méndez et al, 1993;Ludert et al, 1996;Isa et al, 1997;Rolsma et al, 1998). The demonstration that VP4 and VP7, respectively present sites for recognition of α2β1 and α4β1, thought to be RV receptors, suggested alternative way for virus penetration; however sugar residues were not considered (Coulson et al, 1997;Hewish et al, 2000). Wheat agglutinin and ConA were previously shown to inhibit several viruses for binding to true receptors or to inhibit progeny maturation and liberation (Ziegler & Pozos, 1981;Okada & Kim, 1972;Poste et al, 1974;Lonberg-Holm 1975;Cartwright, 1977;Khélifa & Menezes, 1982;Conti & Tsiang, 1985).…”
Section: Discussionmentioning
confidence: 99%